2021
DOI: 10.1111/ijfs.14927
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating effects of fruits and vegetables on gut microbiota – a critical review

Abstract: The objective of the current review was to systematically investigate health-promoting manipulating effects of fruits and vegetables (F&V) on the gut microbiota. The function of gut microbes was found to promote health effects in the host by scavenging free radicals, modulating immune system, alleviating obesity and diabetes. Masters that manipulate the gut microbiota are the phytochemicals within specific types of F&V, where polyphenols account for the largest proportion, along with alkaloids, terpenes, nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 125 publications
0
14
0
1
Order By: Relevance
“…The balance of intestinal flora structure is considered to be an important factor affecting host health, and diet is the main determinant of intestinal flora composition. Dietary intake of fruits and vegetables has been reported to influence the composition of intestinal microorganisms [ 32 ]. In particular, it has been shown that cruciferous vegetables, like cabbage and broccoli, alter the composition of the human gut flora when consumed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The balance of intestinal flora structure is considered to be an important factor affecting host health, and diet is the main determinant of intestinal flora composition. Dietary intake of fruits and vegetables has been reported to influence the composition of intestinal microorganisms [ 32 ]. In particular, it has been shown that cruciferous vegetables, like cabbage and broccoli, alter the composition of the human gut flora when consumed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are a group of antioxidant compounds derived from plants, including phenolic acids, flavonoids, stilbenes and lignin, with high radical scavenging ability that reduces the risk of chronic diseases (cancers and cardiovascular problems) [20]. Polyphenols are reported to actively stimulate the growth of health-boosting microbes, including Lactobacillus, Barnesville and Bifidobacterium, in the human gut while impeding the growth of unhealthy microbes, e.g., Escherichia coli [5]. Polyphenols were found to inhibit α-amylase and α-glucosidase activity together with the modulation of postprandial hyper-glycaemia due to the interaction between starch and polyphenols [21].…”
Section: Fruit Growth and Maturationmentioning
confidence: 99%
“…In the past decade, the utilisation of betacyanin (natural colourants) and pectin from pitaya fruit in food products has been studied. Evidence has reported that beta-cyanins (a type of betalains) derived from red pitaya fruit exhibit antidiabetic effects and modulate glycaemic response [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols, including phenolic and flavonoids, are secondary plant metabolites that can protect against the development of chronic diseases, such as diabetes, osteoporosis, cardiovascular diseases, cancers, and neurodegenerative diseases [44,45]. The ability of plant polyphenols to scavenge free radicals and inactivate other pro-oxidants classifies them among the most powerful antioxidants [46][47][48]. Antioxidant activity of fruit, vegetable, and WGJ was assessed by measuring DPPH radical scavenging activity.…”
Section: Total Phenolic and Flavonoid Content And Antioxidant Capacit...mentioning
confidence: 99%